Choosing and remaining in mental health nursing: Perceptions of Western Australian nurses - Harrison, Carole; Hauck, Yvonne; Hoffman, R. (Wiley-Blackwell Publishing Asia, 2014)
Mental health nursing has an ageing workforce with a critical shortage of nurses in Western Australia. Additionally, mental health is not the preferred career for many graduate nurses.Current challenges with recruitment and retention suggest that strategies are needed to address this issue. This research project adopted a novel approach that focused on exploring the positive aspects of why mental health nurses remain, rather than why they leave. A cross-sectional design was employed comprising a brief interview survey, and nurses working within one public mental health service in Western Australia were invited to participate. A total of 192 nurses participated across 5 months, from adult, older adult, forensic, and education/research programmes. Thematic analysis was conducted from five key questions, and responses from questions one and two are discussed in this paper: ‘Why did you choose mental health nursing?’ and ‘Why do you remain in mental health nursing?’. The main themes extracted in response to choosing mental health nursing were wanting to make a difference, mental health captured my interest, encouraged by others, and opportunities. Subsequent themes extracted from responses to remaining in mental health nursing were facing reality, passion for mental health nursing, patient-centred caring, and workplace conditions. Findings will be utilized to inform strategies for recruitment and retention of graduate nurses; further development of support systems, such as preceptorship training and improving student clinical experiences; as well as improving professional development opportunities for existing mental health nurses.